2020
DOI: 10.1111/sms.13666
|View full text |Cite
|
Sign up to set email alerts
|

Sports participation and sports injuries in Dutch boys with haemophilia

Abstract: Introduction Sports participation in children with hemophilia is generally considered to be associated with increased injury risk, which is generally considered highest in severe hemophilia. Aim To assess sports participation according to age and severity in children with hemophilia and its association with sports injuries. Methods In a retrospective single‐center study, sports participation, injuries, and bleeding data from three consecutive annual clinic visits were collected for young patients with hemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…As in the current study, this study reported high sports participation with 90.5% playing sports (2x/wk; 4.9 h/wk), without comparison with the GP 38 . A retrospective study in Dutch boys with haemophilia (n = 102; age: 6–18) reported similar sports participation to the GP in (77%; 3x/wk) 13 . As in this study, the MAQ was used in studies with Dutch and Australian boys with haemophilia.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As in the current study, this study reported high sports participation with 90.5% playing sports (2x/wk; 4.9 h/wk), without comparison with the GP 38 . A retrospective study in Dutch boys with haemophilia (n = 102; age: 6–18) reported similar sports participation to the GP in (77%; 3x/wk) 13 . As in this study, the MAQ was used in studies with Dutch and Australian boys with haemophilia.…”
Section: Discussionsupporting
confidence: 75%
“…Most studies on sports participation in PWH have reported on children, 10 , 11 , 12 , 13 data of adult PWH are limited. 14 The majority of these studies have reported on the proportion of PWH engaged in sports and type of sports, 15 without considering self‐reported limitations in activities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sports participation in Dutch patients with haemophilia (PWH) has been comparable to the general population (GP), especially in children. 3,4 The recent COVID-19 pandemic has forced governments worldwide to take drastic actions. Although Dutch society has not been in complete lockdown, sports facilities were closed, (outdoor) gatherings of more than three persons were forbidden and social distancing of 1.5 m was mandatory.…”
Section: Sports Participation Of Patients With Haemophilia In the Covmentioning
confidence: 99%
“…With global inequity of access to such care, we are now witnessing children with haemophilia having minimal or no joint damage participating in normal sporting activities similar to their peers, 3 with others in developing countries only beginning to see the benefits of basic physiotherapy interventions on joint health and well-being. 4 The latter example with a younger population with limited access to treatment contrasts further against the emerging clinical issue of an ageing population of men with haemophilia, who are living longer with significant multi-morbidity and significant physical impairment secondary to haemophilic arthropathy.…”
Section: Dear Editormentioning
confidence: 99%